Landslide Surface Prediction with Combined HVSR and VES Geophysical Techniques: Case Study in Semarang City, Indonesia - Andi Fadlan; Hartono Hartono; Antomi Saregar; Vishal R. Panse; Gaurav Rahate; Anita Shukla (International Journal of Hydrological and Environmental for Sustainability, 2024)
Abstract. There are settlements in Tambakaji, Semarang City, which are threatened with landslides because they are located right at the foot of the slope, so research is needed to determine the potential for landslides on the slope. Landslide potential can be identified by identifying the presence of slip planes on the slopes and knowing the soil classification. The prediction of the presence of slip planes is done using the resistivity method while the soil classification uses the HVSR method. The HVSR method is also used to determine the depth of the sediment layer to strengthen the suspicion of the existence of a slip plane in the resistivity method. Based on the results of research using the resistivity method, it shows that the slope has the potential for landslides because it is suspected to have a slip plane at a depth of 20-23 meters (reinforced by the results of the HVSR method which obtains a sediment thickness value of about 23.4 -23.8 meters), but the rate of landslides falls into in the low category because the layer of sediment above it is classified as hard soil.